PERAN EKONOMI MAKRO ISLAM DALAM MENJAGA STABILITAS SOSIAL – EKONOMI INDONESIA AKIBAT GEJOLAK HARGA KEBUTUHAN POKOK - Suci Aldha Eviolla; Oktavia Ramdhani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Fluctuations in the price of basic necessities are a major macroeconomic issue that direcly affects social stability and public walfare in Indonesia. Increases in food prices and other essential goods reduce purchasing power and may widen social inequality and poverty. In this context, Islamic macroeconomics play s a strategic role in maintaining socio – economic stability through principles of justice, balance, and sustainability. The Islamic macroeconomic approach emphasizes the role of the government in stabilitizing prices, strengthingthe real sector, and optimizing wealth distribution instruments such a zakat, infaq, and sadaqah. Moreover, the prohibition of speculative practices, ikhtikar, and riba in Islam serves as an important mechanism to prevent market distortions that may exacerbate price volatility. Through the implementation of Islamic macroeconimic policies oriented toward public welfare, Indonesia’s socio – economic stability can be mainted despite fluctuations in the prices of basic necessities.